Code Mixing In Students’ Conversation at Grade VII in SMP N 2 Pematangsiantar - Silalahi, Marojahan (Pascasarjana Universitas HKBP Nommensen, 2023)
Code mixing can be happened in wide variety of language. It means that, mixing of two or morelanguages can be happened in morpheme/word, phrase, clause, and in sentence. According to Hamers(2000:270) “Code mixing is a language-contact communication strategy, but the speaker of a languagetransfers elements or rules of another language.”The researcher taught that English is important language,The reason to choose code mixing because the researcher found that students try to practice their Englishbut using sometime they have to use code mixing and swithing mostly because of lack of vocabulary.To describe the types of code mixing, to explain the functions of code mixing, and to tell the reasons ofusing code mixing. According to Siregar (1996:50) stated that Code mixing divided into two kinds, intrasentential mixing and extra-sentential mixing.Muysken (2000) defined three types of code mixing, thoseare: Insertion, Alternation, and Congruent Lexicalization.This situation is closer with daily conversationand also describe as their habitual communication. Speech situation of some people this phenomenoncould increase by status in society. In this case, for many young people code mixing becomes their ownstyle which is hoped to look like a modern and educational one.